IMPLEMENTASI MODEL PROJECT BASED LEARNING PADA MATA PELAJARAN SENI RUPA MATERI BATIK ECOPRINT SISWA KELAS IV SDN NGORO 3 - Zhafirah Stabita Qur’aini; Murtyas Galuh Danawati; Siti Fatimah Soenaryo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Cultural arts and skills education in schools is unique because it has meaning and benefits that are used for the developmental needs of students. The population of this study were fourth grade students of SDN Ngoro 3, Ngoro District, Mojokerto Regency, totaling 21 students, including 12 boys and 9 girls. The researcher took class IV of SDN Ngoro 3 as a research subject because during the observation, the author found that for each year class IV of SDN Ngoro 3 made simple batik works with various methods. This discussion contains the results of analysis by researchers with a qualitative descriptive approach. Data collection was carried out using three techniques, namely observation, interviews, and documentation. The implementation of the PjBL Model in Fine Arts subjects regarding ecoprint batik in class IV SDN NGORO 3 began on October 4, 2024. The process begins with soaking the cloth, followed by arranging the leaves, adding dyes, steaming, and finally drying the cloth to dry. In making this ecoprint batik using steaming or steam technique, which will produce a lighter color and the leaf bones appear. And this ecoprint batik uses natural materials that are environmentally friendly.